KORELASI HASIL PEMERIKSAAN SPUTUM BASIL TAHANASAM (BTA) DENGAN GAMBARAN LUAS LESI RADIOLOGI TUBERKULOSIS PARU DI RUMAH SAKITFATMAWATI PADA TAHUN 2018-2019 - Mutiara Fitri Sholina, (2020)
Tuberculosis is an infectious disease that often affects the lungs and has become the highest of the ten causes of death worldwide. There were 10 million people suffering from tuberculosis in 2017 around the world and 1.3 million of them died due to the disease. This event was then designated as a global emergency by WHO. The diagnosis of tuberculosis can be determined based on the patient's main symptoms accompanied by the discovery of mycobacterium tuberculosis bacteria during a bacteriological examination. However, the bacteria are not always found in all patient which means other examinations are required to be conducted, such as radiological examination. The purpose of this study was to determine the relationship between the results of the examination of acid-resistant bacillus sputum (BTA) with extent of area of radiology thoracic lesions in pulmonary tuberculosis patients in Fatmawati General Hospital. This study used a cross-sectional study design by using a consecutive sampling method. Additionally, the study also used up to 40 samples taken from secondary data of medical records of tuberculosis patients in Fatmawati General Hospital during the year 2018-2019. The analysis of the research data is using the Spearman correlation test. After processing the data on SPSS, the value of r is 0.674. Therefore, it can be concluded that there is a relationship between the results of acid-resisstant bacilli (BTA) examination extent of area radiology thoracic lesion in pulmonary tuberculosis patients in Fatmawati General Hospital in 2018-2019.